(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In the past, a person suffering from tuberculosis died regardless of his financial status and age. Today, this disease is not as scary as it was in the past. Despite all the advances in medicine, it can be overlooked, lost, and forgotten.